Chemical exchange saturation transfer effect in blood. Issue 3 (9th May 2013) - Zheng, Shaokuan; van der Bom, Imramsjah M. J.; Zu, Zhongliang; Lin, Guoxing; Zhao, Yansong; Gounis, Matthew J.
<x xml:space="preserve">Abstract</x> Purpose In this report, the feasibility of using blood as an agent for Chemical Exchange Saturation Transfer (CEST) effect is investigated. Methods The CEST effect of porcine blood samples was investigated on a 3.0 T MRI scanner using various power levels and on a 14.1 T NMR spectrometer. As a proof‐of‐concept that CEST can be used to image blood in vivo, the technique was applied in two locations of healthy human volunteers, namely, the femoral artery and the M1‐segment of the middle cerebral artery. Results The blood sample experiments showed that maximum CEST Magnetization Transfer Ratio asymmetry (MTRasym) values of ∼ 12% were achieved, with likely contributions from multiple blood components. These findings were confirmed during the in vivo experiments where CEST signal of blood was clearly greater than surrounding muscular (2%) and brain tissue (3%). Conclusion Ex vivo and in vivo results show that blood is a suitable CEST agent that generates sufficient CEST contrast relative to surrounding tissue. Magn Reson Med 71:1082–1092, 2014. © 2013 Wiley Periodicals, Inc.